Wisdom of Ulū al-Albāb in sustaining human resource development in Muslim world - Mhd. Sarif, Suhaimi (Fakulti Pengurusan Universiti Teknologi Malaysia, 2015)
The wisdom of men that endowed with understanding (ulū al-albāb) sustains human resource development in Muslim world for many centuries despite the presence of colonization and dominance of super power from non-Muslim world. The essence of ulū al-albāb lies with the Tawhīdic paradigm, an Islamic monotheism that guides men and women to execute dual tasks as servant and vicegerent of Allah. This study argues that wisdom of ulū al-albāb provides comprehensive elements of sustainability in the human resource development. Based on interviews with selected Muslim business owners and managers from various nationalities operated their business in Klang Valley, most of the wisdom lies in the struggle to survive within the free market systems and reduces the wisdom of ulū al-albāb to certain routines and innovation instead of survival of the Muslim nation and civilization. The study provides contingency views on human resource development from the ulū al-albāb dimension. Public policy makers and business decision makers would develop ulū al-albāb HRD system to acquire, transfer and nurture wisdom to sustain organization. The future research suggest the study to use triangulation case study method for more rigorous and comprehensive results.